Strong short-range interactions in one-dimensional proton conductor - Stasyuk, I.V.; Vorobyov, O. (Condensed Matter Physics, 2003)
The behaviour of one-dimensional proton conductor is investigated on the
basis of orientational-tunnelling model. The previously proposed technique
which permits the proton interactions to be taken into account in the zeroorder
Hamiltonian, and is based on Green’s function’s expansion in terms
of irreducible Green’s function parts, is generalized. The Larkin equation for
the one-particle proton Green’s function is solved, while irreducible Larkin
part is calculated within the framework of the first order approximation. The
proton energy spectrum and chemical potential behaviour are investigated,
and the results are compared with the ones previously obtained in the
Hubbard-1 type approximation. В роботі вивчається поведінка одновимірного протонного провідника на основі орієнтаційно-тунельної моделі. Узагальнено запропоновану раніше схему, яка дозволяє точно враховувати протонні взаємодії в гамільтоніяні нульового наближення і базується на розкладах функції Гріна за незвідними частинами. Розв’язано рівняння Ларкі-на для одночастинкової функції Гріна у випадку, коли незвідна частина за Ларкіним була розрахована в першому наближенні. Досліджено протонний енергетичний спектр і поведінку хемічного потенціялу, проведено порівняння результатів з раніше отриманими в наближенні типу Габбард-1.